Pengaruh Disiplin Kerja, Motivasi Dan Komitmen Organisasi Terhadap Kinerja Pegawai Pada Badan Kepegawaian Daerah (Bkd) Kabupaten Grobogan(Studi Empiris Di Badan Kepegawaian Daerah Kabupaten Grobogan) - Pria Utama, Hernanta, Dr. Erma Setiawati, Ak, MM (2016)
The research purpose is to know and analyze the influence of labor discipline, motivation, and organizational commitment on employee performance at local staffing agency (BKD) in Grobogan. The population in the study all employees who work at the Regional Personnel Agency (BKD) Grobogan. The sample used was the Regional Personnel Agency (BKD) contained in Grobogan District Government. The sampling technique used purposive sampling with consideration certain criteria. Based on the results of this study found that the variable work discipline known tcount of 3.056> ttable of 2,021, then Ho is rejected (accept H1), which means the work discipline influence on employee performance. Motivation variable value is known tcount 4.198> ttable of 2,021, then Ho is rejected (accept H2), which means the effect of motivation on employee performance. Variable commitment of the organization known tcount 2,976> of 2,021, then Ho is rejected (accept H3), which means that organizational commitment influence on employee performance.